Non-compliance to SAP on local governments in Indonesia: The impact of internal control weaknesses in internal control in accounting and financial reporting and regional complexity - Muhtar Muhtar (University of Merdeka Malang, 2022)
This study attempts to analyze the impact of internal control weaknesses in accounting and financial reporting as well as local government complexity on the non-compliance with Government Accounting Standard (SAP) implementation in Indonesian local governments. Using secondary data from the audit results from the Supreme Audit Board (BPK) on Local Government Financial Reports (LKPD), this study finds that there are still non-compliance with SAP in a number of local governments in Indonesia since the application of accrual-based accounting was required in 2015. On the bright side, the number of non-compliance continues to decrease from year to year. Further, this study reveals that the weakness of internal control in accounting and financial reporting as well as regional complexity has a positive effect on non-compliance with SAP implementation. This research encourages local governments to evaluate and make improvements to the existing internal control weaknesses and accommodate the high complexity level through the development of adequate accounting competencies as well as effective and efficient accounting and financial reporting systems. Thus, local governments can produce LKPD that are compliant with SAP with more reliable and relevant financial information.